Age-Related Cognitive Decline and the Olfactory Identification Deficit Are Associated to Increased Level of Depression - Sanna, Fabrizio; Loy, Francesco; Piras, Raffaella; Moat, Alan; Masala, Carla (Frontiers in Neuroscience, 2021)
Purpose. Previous studies reported a correlation between olfactory function and depression. However, in Literature no data are available for the correlation between depression and all other factors such as age, sex, olfactory, gustatory, cognitive function in healthy subjects taken together. The aim of this study was to provide a systematic account regarding the association between those variables in non-clinical population. Methods. Two hundred and seventy-three participants were recruited with an age range of 19–84 years. Olfactory, gustatory, cognitive function and depression level were evaluated by means of the following tests: the “Sniffin’ Sticks” test, Taste Strips test, Montreal Cognitive Assessment (MoCA) and Beck Depression Inventory (BDI). Results. In our data an age-related decrease in olfactory and gustatory function and a decline in cognitive functions such as attention, memory and language were observed. Instead, no significant differences were observed for the depression level in relation to the different age-ranges. However, our results indicated that the depression level could be associated to sex, odor identification impairment, and decreased attention and language. Conclusions. Sex, the odor identification impairment and an age-related decrease in attention and language are associated with increased level of depression in healthy subjects. Our data can be useful and informative for health-careers in order to act adequate preventive strategies whenever these conditions are detected and recognized.